Features of exciton transport in J-aggregates of amphi-PIC - Malyukin, Yu.V.; Sorokin, A.V.; Lebedenko, A.N.; Efimova, S.L.; Guralchuk, G.Ya. (Functional Materials, 2005)
The experimental results concerning the efficiency of exciton migration under the exciton selective excitation within the amphi-PIC -J-aggregate absorption band at different temperatures are presented. To detect the exciton migration, the luminescence of exciton traps, which are molecules capable of energy capturing as an exciton approaches has been used. Exciton states have been shown to exhibit different mobility within the -J-aggregate absorption band. Excitons in the J-band absorption maximum provide an effective energy transfer to the trap. The efficiency does not change within 20-70 К temperature range and decreases monotonously in the 70-300 К one. At the longer-wavelength edge of the absorption -J-band, excitons are strongly localized. In the 70-300 К range, energy transfer to traps reveals a complicated temperature dependence and activation character. Представлены экспериментальные результаты исследования эффективности миграции экситонов при их селективном возбуждении в пределах полосы поглощения J-агрегатов amphi-PIC при разных температурах. Для детектирования миграции экситонов использовалась люминесценция экситонных ловушек-молекул, способных перехватывать энергию при приближении экситона. Показано, что экситонные состояния в пределах полосы поглощения J-агрегатов обладают разной подвижностью. Экситоны в максимуме полосы поглощения обеспечивают эффективный перенос энергии, который остается неизменным в диапазоне температур 20—70 К и монотонно спадает при изменении температуры в диапазоне 70-300 К. На длинноволновом краю полосы поглощения экситоны сильно локализованы, в диапазоне температур 70-300 К перенос энергии к ловушкам носит активационный характер и имеет сложную немонотонную темпера- Представлено експериментальні результати дослідження ефективності міграції екситонів при їх селективному збудженні у межах смуги поглинання -J-агрегатів amphi-PIC при різних температурах. Для детектування міграції екситонів використовувалася люмінесценція екситонних пасток — молекул, що здатні перехоплювати енергію при наближенні екситону. Показано, що екситонні стани у межах смуги поглинання J-агрегатів мають різну рухливість. Екситони у максимумі смуги поглинання забезпечують ефективний перенос енергії, який залишається незмінним у діапазоні температур 2070 К та монотонно спадає при зміні температури у діапазоні 70-300 К. На довгохвильовому краї смуги поглинання екситони сильно локалізовані, у діапазоні температур 70-300 К перенос енергії на пастки носить активаційний характер та має складну немонотонну температурну залежність.